2011
DOI: 10.1016/j.lfs.2010.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of combinations of digoxin and endogenous cardiotonic steroids on Na+/K+-ATPase activity in human kidney membrane preparation

Abstract: Considering the extensive use of digoxin in the treatment of heart failure and the recent findings that endogenous cardiac glycosides may have altered levels in many diseases, including heart failure, the demonstration of additive effect between cardiac glycosides can help in the understanding of recent clinical observations, including that lower than usual doses of cardiac glycosides are necessary for decreasing mortality in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
(51 reference statements)
2
28
0
Order By: Relevance
“…The sodium-potassium ATPase is targeted by a variety of endogenous and exogenous cardiac glycosides and cardiotonic steroids, with increasing titres of the latter seen in disease states (17). Differing levels of endogenous cardiotonic steroids may partly explain the varied susceptibility to digoxin toxicity, including competition for molecular targets and conformational changes that lead to synergism or antagonism (18,19).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The sodium-potassium ATPase is targeted by a variety of endogenous and exogenous cardiac glycosides and cardiotonic steroids, with increasing titres of the latter seen in disease states (17). Differing levels of endogenous cardiotonic steroids may partly explain the varied susceptibility to digoxin toxicity, including competition for molecular targets and conformational changes that lead to synergism or antagonism (18,19).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…From this point of view, it is of considerable concern that the limited number of past studies that have been done on digitalis sensitivities of the HKE have not been consistent in results and interpretations. 12 15 These studies have had several shortcomings owing to the legitimate difficulties of working with human tissues. First, nearly all of the previous work has been done on recombinant enzymes, 12 14 creating a real possibility that the different membrane environments of the recombinant enzymes may have influenced their digitalis sensitivities.…”
Section: Introductionmentioning
confidence: 99%
“…We were not able to detect the Na C /K C -ATPase a4 isoform at the protein level in Sertoli cells obtained from immature rats (15-day-old), similar to the findings of Woo et al (2000), and found that the Na C /K C -ATPase a1 present in these cells mediates a rapid ouabain-induced signaling cascade, which is to a great extent similar to the rapid signaling pathway triggered by testosterone and E 2 , and plays a role in Sertoli cell proliferation. Interestingly, differently from rodents, the Na C /K CATPase a1 isoform is sensitive to cardiotonic steroids as ouabain (Touza et al 2011).…”
Section: Ouabain Signaling In Rat Sertoli Cellsmentioning
confidence: 97%